Dynamika ustępowania zaburzeń afatycznych a społeczne i poznawcze funkcjonowanie pacjenta. - Filipczak, Sylwia (Logopedia Silesiana, 2015)
The aim of this article is to describe the dynamics of recovery from aphasia of a patient after a neurosurgery. The surgery involved a removal of a haematoma, which was a result of cranio-cerebral injury on the left fronto-temporo-parietal region of the brain. The patient was diagnosed with global aphasia in the first stage of recovery, after the clinical stage had been stabilised. During the rehabilitation period of two years, certain stages of the aphasic disorders occurred. Symptoms of deep receptive and expressive aphasia, with considerable difficulties in understanding and creating verbal expressions, evolved into acoustic-gnostic aphasia with difficulties in identifying the audio form of expression. Phonemic awareness disorders passed soon and acoustic-mnestic aphasia with deficits in auditory-verbal memory followed. Eventually, linguistic disorders transformed into semantic aphasia, including disorders of simultaneous synthesis which caused difficulties in understanding logically and grammatically complex forms of expression, reading and writing. Along with overcoming the aphasic difficulties and the evolution of the linguistic disorders mechanisms, the patient’s level of functioning in social and cognitive sphere was changing. During the process of therapy, which was activating and stimulating the mechanisms of neuroplasticity and neural compensation, the patient additionally acquired a particular aesthetic sensitivity, which resulted in artistic talent and rich artistic output. The speech therapy also inspired the patient to try literary forms of expression. The woman overcame her limitations in reading and writing in order to write her own book. At present, the patient lives a successful life, being involved in its various aspects, such as familial, social and professional ones.